Care of Chickens in an Incubator - Ahmadillo, Soyibjonov; Mamurjonogli, Mirzaev Muhammadsher; Ulugbekqizi, Ahmatova Rozigul (European Journal of Life Safety and Stability (2660-9630), 2021)
This article discusses how to care for, feed, and care for newly hatched chicks.